A study of Filipino complaints in English and Tagalog - Leon, Kristine D. de; Parina, Jose Cristina (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
In order to document Filipino use of complaints in both English and Tagalog, the study sought to analyze their occurrence and relationship between likelihood to complain with regard to gender, perceived level of language proficiency, and status. The study then proceeded with the identification of the semantic formulae of the complaints, and the differences of formulae between females and males when complaining in English and Filipino. The qualitative method revealed that there is no relationship between likelihood to complain and gender and likelihood to complain and self-perceived language proficiency, and that the level of status— superior, equal and inferior does not affect the likelihood of the Filipinos to complain. In addition, this study showed that Filipinos complained in a different manner depending on the language that they used. Filipino males are assertive in complaining in English language while females choose indirect strategies. Both, however, use different semantic formulae in complaining in English and Filipino.